Molecular Dynamics and Quantum Machine Learning Model to Classify Polymorphisms in Multiple Sclerosis - Rueda, Diego; Alves, Levy Bueno; Faria Junior, Milton; Giuliatti, Silvana (Anais do Simpósio Brasileiro de Bioinformática (BSB), 2025)
Multiple Sclerosis is an autoimmune disorder associated with specific HLA-DRB1 alleles however, the structural mechanisms underlying this association remains poorly understood. We developed a model integrating molecular dynamics (MD), machine learning (ML), and quantum neural networks (QNN) to classify alleles as either risk-related or protective. MD simulations of HLA-peptide complexes were conducted, and distance matrices were used as input for a ML-QNN classifier. The combined complex protein (chains A and B) and peptide input resulted in the highest accuracy (0.990) and most stable convergence. This study shows the potential of quantum-classical models in identifying subtle structural patterns linked to autoimmune susceptibility.